Peraturan Hukum tentang Pemberian Hak Tanggungan Tanah - Surya Rianto; Santy Fitnawati WN; Dika Ratu Marfu’atun; Nurhasan Nurhasan (Jurnal Hukum dan Sosial Politik, 2024)
The bill governs the administration of liability-rights. The rights of the liquefied are not divided unless promised in the document the rights are given. If a lien was applied to a certain land right, then it could be agreed upon in the corresponding document of the lien grant, that the payment of secured debts could be made in installments of the same amount as the price of liens. It is part of the title of the load that will be separated from the rights of the load, so the rights of the load in turn weigh only the remainder of the load to secure the rest of the debt. Land rights that can be encumbered with a mortgage are property rights, commercial property rights, and building rights. In addition to the land rights, the land rights of the state that, according to the prevailing regulations of legislation, must be registered and depending on the property that can be deducted, can also be the property rights.